NASCAR 09. - EA Sports (Firm) (Redwood City, CA : EA Sports, 2008)
Complete dynamic challenges to earn contracts in the NASCAR Sprint Cup Series, NASCAR Nationwide Series, and Whelen Modified Tour. With the new easy-to-learn family play mode, anyone can dominate the track to become the NASCAR racing champion.
Title from disc surface.
1 player ; (online 2-14 players) ; 720p supported HD video output ; online ethernet broadband required ; Playstation network compatible ; headset compatible.
ESRB rating: Everyone.
System requirements: PlayStation 3 ; 128 MB required hard disk space ; registration required to access online features.
Blu-ray disc.
106762
Keywords: NASCAR (Association) -- Computer games; Automobile racing -- Computer games; Computer games